Strategi Komunikasi Pemasaran “Lensa Samid” dalam Meningkatkan Pelanggan melalui Instagram - Prasetyo, Dimas; Widiantari, Maria Magdalena; Sejati, Veny Ari (Yayasan Lentera Avanya Nagari, 2024)
Marketing communication assists businesses in providing potential consumers with information about products, how to obtain them, the benefits, and other related information. Digital marketing is an effort to promote a brand using digital media to reach consumers in a timely, personal, and relevant manner. One effective digital marketing tool is social media, such as Instagram, which allows users to publish photos and product information online. This study aims to determine the marketing communication strategy of